Malignant melanoma of the nasal cavity - Maheshwari, Veena (Springer India, 2004)
Malignant melanomas of the sinonasal mucosa are very uncommon, presenting frequently in advanced stages with usually a fatal course. Diagnosis becomes more difficult if it is amelanotic variety. Radical surgery is constrained because of increased morbidity & cosmesis, moreover radiotherapy and chemotherapy have little role if any to play. A case of 60 years old male who presented with nasal mass and epistaxis finally diagnosed as melanoma on histolopathology. Some other important aspects of this rare tumor are discussed here.